The Influence of Product Quality and Digital Marketing on Telkomsel Card User Satisfaction Moderated by Brand Image at CV Sinar Telekom - Pulungan, Tio Candra; B, Mesra; Harianto, Harianto (Jurnal Fokus Manajemen, 2026)
Objective: This study aims to determine the effect of product quality and digital marketing on Telkomsel cardholder satisfaction, moderated by brand image at CV Sinar Telekom. Research Methodology: This study is quantitative. The subjects were consumers who purchased Telkomsel cards at CV Sinar Telekom. A sample of 100 respondents was drawn using an unanticipated sampling technique based on the Lemeshow formula. Data were analyzed using descriptive statistics and Partial Least Squares Structural Equation Modeling (PLS-SEM).Results: The results indicate that customer satisfaction is not influenced by product quality. However, customer satisfaction is influenced by digital marketing. In addition, brand image moderates the effect of product quality and digital marketing on customer satisfaction. Limitations: This study only covers Telkomsel cardholders at CV Sinar Telekom and the sample size is limited, so generalizing the results to a wider population requires caution. Contribution: This study contributes to the field of marketing and brand management, particularly in digital marketing strategies and customer satisfaction development in the telecommunications industry.